The Role of streetscape properties to Achieve User’s Aesthetic Response - Rawaa Fawzi Naom; Neda Khalil Ibrahim (Iraqi Journal of Architecture and Planning, 2018)
Urban spaces, as part of the city that could shape landscape are needed to form an essential systemic part of the city and due to the lack of streetscape as part of the city landscape to the demands and that achieves user’s respond and interact.This study is concerned with user’s demands related to streetscape and the role that is played by it’s various elements through a responsive design to user’s needs from an aesthetic point of view, The hypothesis of this study is manifested through “Disparity and deferential user’s aesthetical response to the various characteristics of streetscape as relevant to user’s movement through these spaces.The study depended on dealing with user’s aesthetic response throughout various characteristics of streetscape to achieve that response over specific movement types (linear, grid, curved, fragmented) which can be identified by the user, perceived and then respond to it.The research reach most important landscape elements which achieves aesthetic response through streetscape properties (greenscape, floorscape, benches and seating, vertical elements, waterscape) also most important user’s movement types that achieves aesthetic response through streetscape properties (curved, grid, linear, fragmented).Finally the research reach a comprehensive theoretical model for the role of landscape elements to achieve user’s aesthetic response in streetscape throughout movement types and then the research gave a list of recommendations. Key Word: Streetscape, Landscape, Aesthetic response, streetscape properties.